Effect of gamma irradiation on the inactivation of aflatoxin B1 and fungal flora in peanut - Prado,Guilherme (2003)
The effect of gamma irradiation on aflatoxin B1 levels and fungal infection were investigated in peanut samples, Tatu Vermelho cultivar. At a radiation dose of 10 KGy, growth of molds was completely inhibited. Doses of 15, 20, 25 and 30 KGy were sufficient for destruction of aflatoxin B1 by 55-74%. The results suggested that the decontamination of molds by irradiation, before production of aflatoxin B1, is the most acceptable method in the preservation of peanut.